2015
DOI: 10.3109/10520295.2015.1048289
|View full text |Cite
|
Sign up to set email alerts
|

Comparative performance analyses of commercially available products for salivary collection and nucleic acid processing in the newborn

Abstract: Analysis of saliva for clinical monitoring and biomarker detection holds great promise for improving health care. Commercially available assays are not intended for use with neonates, however, and collection and processing of saliva for subsequent transcriptomic analysis presents unique challenges in this population. We compared RNA yield, quality, stability and RT-qPCR performance for two commonly used commercial systems: the Qiagen RNeasy Protect Saliva Mini Kit® and the DNA Genotek Oragene•RNA® assay. Two 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…Indeed, a study using human cell and tissue samples subjected to total RNA purification after longitudinal heat degradation has demonstrated that RIN values rapidly decrease with heat exposure and housekeeping messenger RNAs are lost to detection, whereas miRNAs remain remarkably stable over time. 48 Despite the limits associated with RIN reporting, we note that the average RIN for this dataset exceeded RIN values reported in previous saliva RNA studies 49 ; there was no difference in average RIN among the ASD, TD, and DD groups; and RNA-ADOS correlations were actually strengthened when RIN was added as a covariate. We encourage any future studies using saliva RNA measures to use stringent methods for RNA stabilization and extraction and to carefully assess the influence of RNA integrity on biomarker findings.…”
contrasting
confidence: 52%
“…Indeed, a study using human cell and tissue samples subjected to total RNA purification after longitudinal heat degradation has demonstrated that RIN values rapidly decrease with heat exposure and housekeeping messenger RNAs are lost to detection, whereas miRNAs remain remarkably stable over time. 48 Despite the limits associated with RIN reporting, we note that the average RIN for this dataset exceeded RIN values reported in previous saliva RNA studies 49 ; there was no difference in average RIN among the ASD, TD, and DD groups; and RNA-ADOS correlations were actually strengthened when RIN was added as a covariate. We encourage any future studies using saliva RNA measures to use stringent methods for RNA stabilization and extraction and to carefully assess the influence of RNA integrity on biomarker findings.…”
contrasting
confidence: 52%
“…Collecting neonatal salivary samples presents unique challenges since only small amounts of saliva can be sampled using commercially available kits (Table S1). However, small modifications to existing protocols have produced successful results allowing for the collection of samples as small as 10 μL . Unstimulated saliva secretion is higher in healthy males, younger than 44 years, due to the size of salivary glands which are larger than those in females, indicating sex-dependent secretion.…”
Section: Methods For Sampling and Collecting Salivamentioning
confidence: 99%
“…The preprocessing time varies and can reach up to 24 h before analysis for some stabilizing saliva kits, which may be an issue when high throughput is needed . Sample stability can be achieved for various periods, ranging from days to up to one month at room temperature, or even longer at lower temperatures (−20, −80 °C). ,,, The effectiveness of stabilization may affect not only the storage period but also the yield and the quality of the extracted RNA. ,, Stabilizing solutions are usually provided in collection tubes. This type of collection device can be extremely useful during daily clinical operations, as the stabilizing effect starts immediately during sample collection.…”
Section: Stabilization Approaches For Salivary Biomarkersmentioning
confidence: 99%
“…Without stabilization, the sample's microbial community is likely to change during transit, and their molecular components may deteriorate before the DNA is extracted [12] , [13] , [14] , therefore influencing the metagenomic results obtained. To overcome this problem, commercial stabilizers have been developed to preserve the microbial community and its DNA while removing the need for immediately freezing the samples [15] , [16] , [17] . Stabilizers can be employed for sampling in remote field locations, for the delivery of biological samples, or for at-home sampling kits for humans.…”
Section: Introductionmentioning
confidence: 99%